2019
DOI: 10.17535/crorr.2019.0003
|View full text |Cite
|
Sign up to set email alerts
|

Jordan neural network for inflation forecasting

Abstract: In times of pronounced nonlinearity of macroeconomic variables and in situations when variables are not normally distributed, i.e. when the assumption of i.i.d. is not fulfilled, neural networks (NNs) should be used for forecasting. In this paper, Jordan neural network (JNN), a special type of NNs is examined, because of its advantages in time series forecasting suitable for inflation forecasting. The variables used as inputs include labour market variable, financial variable, external factor and lagged inflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(55 reference statements)
1
4
1
Order By: Relevance
“…These findings support our modeling strategy when neural networks are considered in practical applications, i.e., for forecasting purposes. This is in line with [18,38] who found that multivariate models and more variables can improve inflation forecasts, while it is opposite to findings of [24,28] favoring simpler models. The same conclusion emerges when JNNs are compared with appropriate ARIMA models.…”
Section: Empirical Results and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings support our modeling strategy when neural networks are considered in practical applications, i.e., for forecasting purposes. This is in line with [18,38] who found that multivariate models and more variables can improve inflation forecasts, while it is opposite to findings of [24,28] favoring simpler models. The same conclusion emerges when JNNs are compared with appropriate ARIMA models.…”
Section: Empirical Results and Discussionsupporting
confidence: 80%
“…Ref. [24] compared JNN only with different exogenous inputs to conclude that in most cases the simplest JNNs are ranked the highest by their performance, i.e., JNNs with lagged dependent variable and one exogenous regressor. Ref.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The classical Box-Jenkins Models only work with linear data, whereas the machine learning models (RNN) work well on a wide range of data including nonlinear data. Furthermore, as per the research regarding the prediction of agriculture commodities prices in developing countries like India [13][14][15][16][17][18][19] , Recurrent Neural Network is specified best for nonlinear, adaptable, and strongly mapped data. Therefore, we will be using the LSTM (special recurrent neural network) model, over other models like the ARIMA model, for predicting the agriculture commodity price.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Poyser [22] has not found any relevant effect of confirmation time, hash rate, and the number of transactions per day on Bitcoin's price, which is contrary to results from [16] and [9] that show a positive, albeit small, effect of blockchain variables on Bitcoin's price. When it comes to sentiment analysis measures, most researchers agree that attractiveness is the main driver of Bitcoin price ( [22], [10], [24], [23]). Even though there is no consensus regarding the impact of macro-finance factors on Bitcoin prices, the macro-finance variables most usually associated with Bitcoin prices are the S&P500, gold, oil, real estate, VIX, and exchange rates.…”
Section: Introductionmentioning
confidence: 99%